Phenomenon Sediment Transport in The Channel to The Change Distance of Check Dam Series - Putri Permata Sari; Darwizal Daoed; Nurhamidah (Universitas Negeri Padang, 2025)
This study investigated the flow and sedimentation patterns at a series of check dams on the Kuranji River. A physical model was built in the laboratory at a specific scale to simulate field conditions. The models were built using an approach to existing conditions with a dam height scale of 1:125 while the check dam spacing was 1:300 while the field condition spacing between check dams of scenario 1 (89.00 cm), scenario 2 (94.00 cm), scenario 3 (200 cm). All models were conducted in a 40 x 40 cm rectangular open channel in the laboratory of Fluid Mechanics and Hydraulics, Faculty of Engineering, Andalas University, Padang. Sediment material was used from the Kuranji Trunk. Furthermore, each experiment with variations in flow discharge was observed and measured the sediment distribution pattern before and after the check dam building. From the test results, it was found that the sediment balanced condition ranged from 10-19 minutes after the water came out of the dainhole. Sediment distribution patterns are influenced by two main factors, namely the distance between check dams and flow discharge. The use of too far a distance results in sediment having a greater chance of moving away downstream, on the other hand, with a close distance between check dams, the sediment distribution moves not too far. Discharge variations affect the scouring depth. The greater the flow discharge, the greater the energy to scour and carry the greater sediment.